A clinical study of pneumonia with special reference to hyponatremia among children aged 1–5 years admitted in teaching hospital - Dr. Jayaraj Patil; Dr. Srinivasa Arer (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Pneumonia probably is one of the oldest diseases, as old as antiquity known to human kind and has always remained a subject of challenge to medical science, despite extensive research. Hyponatremia is the most common electrolyte disorder among hospitalized patients and has been associated with increase in mortality.Objectives: 1) To study clinical profile of pneumonia among children aged 1-5 years. 2) To determine the frequency of hyponatremia in pneumonia.Methodology: This was a hospital based cross sectional study of pneumonia with special reference to hyponatremia conducted among children aged 1-5 years who were admitted in pediatric wards of Assam Medical College Dibrugarh, Assam, during the period April 2012 to March 2013.Results: In the present study, outof 300 cases of pneumonia, 78 (26%) cases were hyponatremic. Among them 9 (11.5%) cases were pneumonia, 51 (65.4%) cases were severe pneumonia and 18 (23.1%) cases were very severe pneumonia. Mean duration of hospital stay of patient with hyponatremia with pneumonia was 9.54 ± 2.63 and those with normonatremia with pneumonia were 6.43 ± 1.16.Conclusion: Incidence of hyponatremia in pneumonia is common and its incidence is more common in cases of very severe pneumonia. Mean duration of hospital stay of patient with hyponatremia with pneumonia is more compared to those with normonatremia with pneumonia.